KEANEKARAGAMAN GENETIK SALACCA ZALACCA BERDASARKAN PENANDA AFLP - Zumaidar Zumaidar; Tatik Chikmawati; Alex Hartana; Sobir Sobir (Floribunda, 2015)
Salacca zalacca has two varieties, namely Salacca zalacca var. zalacca called salak Jawa and Salacca zalacca var. amboinensis called salak Bali. Based on agronomical and morphological characters, people have known several cultivars of both varieties. This study aims to determine the genetic differences between them. Salak samples (Salacca zalacca) accounted for 91 accessions from Aceh, West Java (Bogor, Sumedang, Tasikmalaya), Central Java, Jogjakarta, and Sulawesi, included 22 cultivars consisted of 11 released cultivars and 11 local cultivars. Molecular marker was used Amplified Fragment Length Polymorfism markers (AFLP) that consisted of two different primer combinations are EcoRI-ACT and Mse1-CAT; and EcoRI-ACC and Mse1-CTT. Data were analyzed using the UPGMA method. The results showed that the data fragments that were scored from the combination of two different primer were 531. Those were polymorphic on the size of 140–489 bp for ACT-CAT and 140–447 bp for ACC-CTT. Primer combinations of EcoRI-ACC and Mse1-CTT produced polymorphic data moresomore efficiently than primer combination of EcoRI-ACT and Mse1-CAT. Phenetic analysis illustrates the genetic relationship between salak Jawa and salak Bali on 0.61 similarity coefficient. Dendrogram showed union of salak Bali accessions at tree branches. Molecularly AFLP markers indicated separation of salak Jawa and salak Bali.